Milk exosomes and miRNA cross the placenta and promote embryo survival in mice. Issue 4 (October 2020) - Sadri, Mahrou; Shu, Jiang; Kachman, Stephen D; Cui, Juan; Zempleni, Janos
Abstract : Exosomes facilitate cell-to-cell communication by transferring regulatory molecules such as miRNA from donor to recipient cells, for example, miR-21-5p and miR-30d promote placentation. Exosomes and their miRNA cargos are not exclusively obtained from endogenous synthesis but may also be absorbed from dietary sources, such as milk. This study assessed the effects of milk exosomes and miRNA cargos on embryo development and fertility in C57BL/6 mice. Fluorophore-labeled milk exosomes, miR-21-5p and miR-30d accumulated in murine placenta and embryos following oral gavage. Seventeen mRNAs, miR-21-5p and miR-30d were differentially expressed in placentas of pregnant mice fed a milk exosome and RNA-depleted (ERD) diet or a milk exosome and RNA-sufficient (ERS) diet. Eight of these mRNAs encode proteins implicated in the synthesis of extracellular matrix components, cell adhesion and migration. Changes in mRNA expression were associated with corresponding changes in protein expression, for example, collagen type I. The size of litters born to dams fed ERD was 25–50% smaller than those born to ERS controls. This study implicates dietary exosomes and miRNA in placenta development and embryo survival.